2020
DOI: 10.1186/s12645-020-00060-w
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the effective dose of cisplatin using gold nanoparticles as carriers

Abstract: Background The increasing rate of cancer cases is alarming. In 2018, 9.6 million people died of the disease (WHO 2020). Current treatments, such as chemical therapy using cisplatin (CisPt) as a basis, cause considerable collateral damage to the patient (Ahmad 2017). CisPt acts as an alkylating agent with affinity to DNA, binds to the guanine and cytosine residues, and prevents the processes of replication and transcription of the genetic material, resulting in cell death by apoptosis (Ahmad 2017). However, cis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 44 publications
(45 reference statements)
2
10
0
Order By: Relevance
“…Furthermore, GNPs could be used as a cisplatin delivery vehicle [ 72 ]. A recent study showed that if GNPs are used as drug carriers, the amount of cisplatin necessary to cause the desired cytotoxic effect would be less than the amount used in conventional cancer treatments [ 72 ].…”
Section: Prospects Of Using Gnps With Other Radiosensitizersmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, GNPs could be used as a cisplatin delivery vehicle [ 72 ]. A recent study showed that if GNPs are used as drug carriers, the amount of cisplatin necessary to cause the desired cytotoxic effect would be less than the amount used in conventional cancer treatments [ 72 ].…”
Section: Prospects Of Using Gnps With Other Radiosensitizersmentioning
confidence: 99%
“…Furthermore, GNPs could be used as a cisplatin delivery vehicle [ 72 ]. A recent study showed that if GNPs are used as drug carriers, the amount of cisplatin necessary to cause the desired cytotoxic effect would be less than the amount used in conventional cancer treatments [ 72 ]. For example, IC 50 diminished approximately 7 times, compared to the IC 50 of cisplatin used alone, when using GNPs as delivery vehicles (see Figure 6 ) [ 72 ].…”
Section: Prospects Of Using Gnps With Other Radiosensitizersmentioning
confidence: 99%
See 1 more Smart Citation
“…As most studies have mainly focused on tumor cells, our study is designed to elucidate the NP interactions in tumor cells and in CAFs. We used gold nanoparticles (GNPs) as our model NP system, since they can be used as a radiation dose enhancer in radiotherapy and a drug carrier in chemotherapy [15][16][17][18][19]. The biocompatibility of GNPs has been determined in a phase I clinical trial [20].…”
Section: Introductionmentioning
confidence: 99%
“…Among other NP systems, we used GNPs as a model NP system for this study due to their promising results in several practiced clinical applications including RT and CT as described in Fig. 1 (left most) (Chithrani et al 2010 ; González-López et al 2020 ; Khoo et al 2017 ; Paciotti et al 2016 ). Biocompatibility of GNPs and their ability to act as a vector for targeted drug delivery to the tumor were demonstrated successfully in a phase I clinical trial (Libutti et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%